Penyimpanan Mahkota Nanas dan Zat Pengatur Tumbuh pada Pertumbuhan Setek Basal Daun Asal Mahkota - Putri Mian Hairani; Mohamad Rahmad Suhartanto; Eny Widajati (Institut Pertanian Bogor, 2020)
The availability of pineapple seedlings in the field is a problem in the development of Smooth cayenne pineapple because of limited sources of planting material compared to the other types. Effort that can be done to solve the problem is to use the method of crown leaf-bud cutting. Propagation of pineapple (Ananas comosus L) with the method of crown leaf-bud cutting is not optimum so it can be optimized; one of them is by giving the duration of storage treatment and application of plant-growth regulators. The experiment was aimed to study the effect of crown storage duration and plant growth regulators on the growth of pineapple seedlings. The experiment was arranged in a nested plot design. Duration of crown storage for 2 (control), 10, and 20 days in room conditions at a temperature of 29-35°C and humidity of 46-70% as the main plot. The subplot was combination of indole-3-butyric acid (IBA) and 6-benzylaminopurine (BAP) with the concentrations: IBA 300 ppm and BAP 400 ppm, IBA 300 ppm and BAP 600 ppm, IBA 400 ppm and BAP 400 ppm, as well as IBA 400 ppm and BAP 600 ppm. The results of the experiment showed that the leaf-bud cuttings which stored for 10 days 57.34% were survived, 57.15% were sprouted, and 51.62% were rooted, while the control that survived, sprouted, and rooted did not reach more than 30%. The content of endogenous ABA in the crown leaf-bud shoots decreased significantly after being stored for 10 and 20 days, while the contents of endogenous auxins and cytokines were not different from the controls. Application of IBA 400 ppm combined with BAP 400 and 600 ppm increased the percentages of survived and sprouted cutting 1.5-1.7 times compared to control. Keywords: auxin, cytokines, exogenous hormone, endogenous hormone, vegetative propagation